x-3(7+2x)=

Simple and best practice solution for x-3(7+2x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3(7+2x)= equation:


Simplifying
x + -3(7 + 2x) = 0
x + (7 * -3 + 2x * -3) = 0
x + (-21 + -6x) = 0

Reorder the terms:
-21 + x + -6x = 0

Combine like terms: x + -6x = -5x
-21 + -5x = 0

Solving
-21 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + -5x = 0 + 21

Combine like terms: -21 + 21 = 0
0 + -5x = 0 + 21
-5x = 0 + 21

Combine like terms: 0 + 21 = 21
-5x = 21

Divide each side by '-5'.
x = -4.2

Simplifying
x = -4.2

See similar equations:

| 36x-(36/x^2)=0 | | -3(-9w+2)-9w+2(w-8)-8= | | X/2-7=7 | | 2500/y=500 | | 2x+2(5x+3)=74 | | x*2-9x=36 | | 2(5)+2(x)=40 | | 7x-3x+12=4x+6x | | 5/13 | | 2x+3-(-1+1x)=2x-2-x | | 5(3s+2m)= | | 8m-4(-5m+3)= | | (b-b^(1/3))/(b^(1/3)-1) | | y-3=-3(x+3) | | 4(x+2)-7=2x+2(-1+x) | | 11+8x-11-6x+6=11+(8x-11)-6x+6 | | 4(n-5)+15n=-4(-10n+3)-21n-8 | | 16=0 | | (x-3)x(x-5)= | | 5(3x-6)=9x-12 | | y-3=-3(x+3) | | y-3=-3(x-1) | | y+3=-3(x-3) | | k-16=-36 | | 4y+2=x | | -7t/2=7 | | y+3=-3(x+1) | | 3+2x-9=5x-21 | | 4xsquared+100=0 | | -3(5x+3)-2(x-6)= | | 1/2x2-3 | | c-79.9=-104.9 |

Equations solver categories